Improving Student Learning Outcomes with the Make a Match (MaM) Method in Science Subjects in Class VA SD Negeri 15 Kota Sorong - Fuad Rahmatullah, (SEARCH: Science Education Research Journal, 2025)
This study aims to improve student learning outcomes through the use of the Make a Match method in science subjects on the material of Blood Circulatory Organs and Their Functions in class V A SD Negeri 15 Sorong City. This paper is a class action research (PTK) with data collection techniques using test methods, field notes, and documentation. Data processing and analysis techniques use descriptive statistics by presenting data in the form of tables/graphs, calculating averages, and percentages using Excel. The standard/KKM is 70. The results of this study show that: 1) The average value of student learning outcomes in cycle I was 72. There were 16 students who were complete with a percentage of 67%, while there were 8 students who were not complete with a percentage of 33%. 2) The average student learning outcomes in cycle II was 79. The number of students with complete criteria was 24 people or 100%. This means that the action in cycle II, namely the use of the Make a Match (MaM) method in science subjects on the material of Blood Circulatory Organs and their Functions in class V A, is stated to be able to improve student learning outcomes.